Magnetic resonance-based thermometry during laser ablation on ex-vivo swine pancreas and liver. Issue 7 (July 2015) - Allegretti, G.; Saccomandi, P.; Giurazza, F.; Caponero, M.A.; Frauenfelder, G.; Di Matteo, F.M.; Beomonte Zobel, B.; Silvestri, S.; Schena, E.
Highlights: We provided first data of magnetic resonance (MR) thermometry on pancreas. We tested the effectiveness of two T 1 -wighted sequences for MR-based thermometry on liver, and afterward on pancreas. Fiber Bragg Grating sensors (FBGs) were employed for reference temperature monitoring. We investigated laser ablation (LA) on pancreas as possible novelty in clinical practice. Abstract: Laser Ablation (LA) is a minimally-invasive procedure for tumor treatment. LA outcomes depend on the heat distribution inside tissues and require accurate temperature measurement during the procedure. Magnetic resonance imaging (MRI) allows a non-invasive and three-dimensional thermometry of the organ undergoing LA. In this study, the temperature distribution within two swine pancreases and three swine livers undergoing LA (Nd:YAG, power: 2 W, treatment time: 4 min) was monitored by a 1.5-T MR scanner, utilizing two T 1 -weighted sequences (IRTF and SRTF). The signal intensity in four regions of interest, placed at different distances from the laser applicator, was related to temperature variations monitored in the same regions by twelve fiber Bragg grating sensors. The relationship between the signal intensity and temperature increase was calculated to obtain the calibration curve and to evaluate accuracy, sensibility and precision of each sequence. This is the first study of MR-based thermometry during LA on pancreas. More specifically, the IRTF sequence provides the highest temperature sensitivity in both liver (1.8 ± 0.2 °C −1 ) and pancreas (1.8 ± 0.5 °C −1 ) and the lowest precision and accuracy. SRTF sequence on pancreas presents the highest accuracy and precision (MODSFRT = −0.1 °C and LOASFRT = [−2.3; 2.1] °C).